Procrastination in medical students: A systematic review - Rahimi, Sonia; Chichekian, Tanya; Lee, So Yeon (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2026)
Background: The purpose of this systematic review was to understand the implications of procrastination on medical students’ lives and well-being by examining its conceptualization in the medical education literature, the contexts in which it has been studied, and with which variables it has been associated. These areas were investigated to propose practical solutions to reduce medical students’ procrastination tendencies.Methods: This systematic review was completed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses and the guidelines of the Association for Medical Education in Europe. We searched the PubMed, ERIC (ProQuest), and PsycINFO (OVID) databases. A total of 243 articles were identified and screened independently by two authors.Results: Based on a set of inclusion criteria, 26 articles were kept and analyzed in the review. We found that medical students’ procrastination was most often conceptualized as the voluntary delay of a given task. Medical students’ procrastination was examined in two different contexts: academic procrastination and bedtime procrastination. Procrastination was negatively related to variables such as academic achievement, metacognition, and self-esteem, and positively related to other variables such as stress, anxiety, and mobile phone addictions.Conclusions: Medical students’ procrastination is most frequently described as the intentional or voluntary postponement of a given task with the expectation of negative consequences and is most often evaluated in academic settings alongside mental health and affective variables. Future research should focus on promoting students’ awareness of their procrastination and emotional states through targeted and goal-oriented interventions.